ARTIFICIAL INTELLIGENCE AND AUGMENTED REALITY: THE NEXUS OF SCIENCE, LEARNING, AND INDUSTRY - Sania, Umme (Журнал математики и информатики, 2024)
This research paper explores the role of artificial intelligence (AI) in conjunction with augmented reality (AR) in enhancing integration across science, education, and production domains. AI, with its machine learning algorithms and predictive analytics, has revolutionized data processing, decision-making, and automation. AR, on the other hand, overlays digital information onto the physical world, creating immersive and interactive experiences. By combining these technologies, new avenues for seamless integration emerge, leading to enhanced collaboration, efficiency, and innovation. The paper analyzes the applications of AI and AR in optimizing production processes, personalizing educational experiences, and fostering collaborative research platforms. Real-world case studies and practical implementations demonstrate the transformative impact of AI and AR integration, while ethical considerations and challenges are also discussed to ensure responsible deployment.